TI_GERICHTE 52.2013.11 vom 30. Dezember 2013 , Designazione del delegato comunale nel consiglio di amministrazione di una SA - TI Tribunale d'appello (2013)
Designazione del delegato comunale nel consiglio di amministrazione di una SA